A Preliminary Report of the Survey on Teaching Strategies, Phase 1 An Evaluation by Students in the A.B. English, A.B. Filipino, and A.B. History Programs - Baguio, Darwisa A.; Flores, Lorna E.; Castro, Luz C. Sevidal; Arquisal, Amabelle B. (2010)
This article is based on data templates contained in the reports delivered during a research forum at the College of Arts and Social Sciences. The College Research Forum, "Report on the Highlights of the Survey on Teaching Methods and Strategies," was held on 9 August 2010 at the CASS Bulwagang Filipino. The data templates were culled from the survey of graduating students' evaluation of the effectiveness of teaching methods and strategies. The survey referred, in general, to students' perspectives about the methods employed in the foundation courses at the CASS, as well as, those used in the teaching of major courses of the respective students' programs. The initial phase of this survey was conducted in 2007 simultaneously in the six (6) degree programs of the College. In that survey, the graduating students rated the techniques employed in the subjects (foundation courses and major courses) that they had taken at the CASS. These techniques had been grouped into methods clusters for Skills, Learning Activities, Resource Materials, and Evaluation.

The main basis for this writeup consists of the mean scores computed from the results of the aforementioned survey in which the respondents were the graduating students of the Department of English, Departamento ng Filipino at Ibang Wika, and the Department of History.
Keywords: Filipino language -- Study and teaching; English language -- Composition and exercises -- Study and teaching (Higher); History education